Discovery and prospects of new heterocyclic Isatin-hydrazide derivative with a novel role as estrogen receptor α degrader in breast cancer cells - Arif, Muhammad Nouman; Sarwar, Sadia; Firdous, Farhat; Saleem, Rahman Shah Zaib; Nadeem, Humaira; Alamro, Abir Abdullah; Alghamdi, Amani Ahmad; Alshammari, Atekah Hazza; Farooq, Omer; Khan, Rashid Ali; Faisal, Amir (Frontiers in Chemistry, 2024)
Isatin, a heterocycle scaffold, is the backbone of many anticancer drugs and has previously been reported to engage multiple cellular targets and mechanisms, including angiogenesis, cell cycle, checkpoint pathways and multiple kinases. Here, we report that a novel isatin derivative, 5i, degrades estrogen receptor alpha (ERα) in estrogen mediated breast cancer cells. This effect for istain nucleus is not reported before in literature.Tamoxifen and fulvestrant represent standard therapy options in estrogen mediated disease but have their own limitations. Isatin-based triple angio-kinase inhibitor BIBF1120 is in phase III clinical trials, while Sunitinib III (Sutent), a multikinase inhibitor has been approved by FDA. Keeping this in view, we synthesized a series of N'-(1-benzyl-2-oxo-1, 2-dihydro- 3H-indol-3-ylidene) hydrazide derivatives and evaluated those in vitro for antiproliferative activities in MCF-7 (ER+) cell line. Compound 5i showed the best results (IC50 value;9.29 ± 0.97µM) in these cells. Furthermore, 5i downregulated ERα protein levels in a dose-dependent manner in MCF-7. The multifaceted analysis of multiple physicochemical properties was carried out by Data Warrior software which pointed out some very prominent features that qualify the synthesized compounds as the promising drug candidates. We used in silico pharmacokinetics prediction tools, particularly pkCSM tool, for the assessment of the activity profiles of the compounds. The docking studies were undertaken to predict the binding affinities of the ligands (compounds) with the target protein (ERα). The docking scores were calculated in terms of binding affinities. Molecular dynamics (MD) simulation was used to analyze and evaluate the stability and dynamic behavior of the protein-ligand complex between ERα and its ligand 5i. Overall, these results suggest that the new isatin derivative 5i holds promise as a new ERα degrader.